Role of environmental factors in shaping spatial distribution of salmonella enterica Serovar Typhi, Fiji - de Alwis, R; Watson, C; Nikolay, B; Lowry, JH; Thieu, NTV; Van, TT; Ngoc, DTT; Rawalai, K; Taufa, M; Coriakula, J; Lau, CL; Nilles, EJ; et al. (Centers for Disease Control and Prevention, 2018)
Fiji recently experienced a sharp increase in reported typhoid fever cases. To investigate geographic distribution and environmental risk factors associated with Salmonella enterica serovar Typhi infection, we conducted a cross-sectional cluster survey with associated serologic testing for Vi capsular antigen-specific antibodies (a marker for exposure to Salmonella Typhi in Fiji in 2013. Hotspots with high seroprevalence of Vi-specific antibodies were identified in northeastern mainland Fiji. Risk for Vi seropositivity increased with increased annual rainfall (odds ratio [OR] 1.26/quintile increase, 95% CI 1.12-1.42), and decreased with increased distance from major rivers and creeks (OR 0.89/km increase, 95% CI 0.80-0.99) and distance to modeled flood-risk areas (OR 0.80/quintile increase, 95% CI 0.69-0.92) after being adjusted for age, typhoid fever vaccination, and home toilet type. Risk for exposure to Salmonella Typhi and its spatial distribution in Fiji are driven by environmental factors. Our findings can directly affect typhoid fever control efforts in Fiji.